Traveling Waves in Degenerate Diffusion Equations (Communications in Mathematical Research, 2022)
In this survey, we present a literature review on the study of traveling waves in degenerate diffusion equations by illustrating the interesting andsingular wave behavior caused by degeneracy. The main results on wave existence and stability are presented for the typical degenerate equations, includingporous medium equations, flux limited diffusion equations, delayed degenerate diffusion equations, and other strong degenerate diffusion equations.
Keywords: Traveling waves; degenerate diffusion equation; existence; stability.